Determination of R, LS, C and P factors in universal soil loss equation for kuantan River Basin - Vivian, Lee Kah Yee (2018)
The Universal Soil Loss Equation (USLE) model is used to estimate average soil loss generated from Kuantan River Basin. Use of the USLE has recently been extended for predicting soil loss and plan control practices in agricultural catchment by the effective integration of Geographic Information Systems (GIS) based on procedures to estimate the factor values in a grid cell basis. This study was performed to predict the soil erosion rate using the USLE/GIS methodology for planning conservation measures in the site. Rainfall erosivity (R), topographic factor (LS), cover management factor (C) and erosion management practices factor (P) values for the model were calculated from rainfall data as well as topographic and land use maps. Rainfall erosivity factor was generated by using rainfall erosivity map in Guideline for Erosion and Sediment Control Malaysia and it is found that the nearer is the location to the coast, the higher is the R factor. Next, LS factor is calculated by using an equation where the slope length and slope steepness are extracted from the topography map. Lastly, C and P factors of each sub basin are generated by using ArcGIS software. C and P values are extracted from previous studies and are assigned to each unique polygon base on their landuse and landcover properties. The closer are the C and P factors to 1, the less effective arethe landcover and erosion control practices in reduce erosion. The results show that annual erosion rate for each sub basin in Kuantan River Basin varies between 0.24 to 400.61t/ha/year according to USLE.